Actinomyces europaeus Isolated from a Breast Abscess in a Penicillin-Allergic Patient - Sarah E. White; Stephen D. Woolley (Case Reports in Infectious Diseases)
This is a case of Actinomyces europaeus in the breast abscess of a penicillin-allergic woman. The mainstay of treatment for actinomycosis is penicillin, and there is a lack of literature describing nonpenicillin treatment options. A 69-year-old woman presented acutely with a breast abscess which was managed with incision and drainage and antibiotic therapy to good response. 21 days after presentation, Actinomyces were grown from the culture of pus, so the patient was recalled and more rigorous treatment and follow-up were initiated. The penicillin allergy led to difficulty in the identification of an appropriate antimicrobial agent that was also logistically feasible to be given on an outpatient IV basis. IV tigecycline followed by oral clarithromycin was found to be effective treatment.